2011
DOI: 10.1016/j.fertnstert.2011.09.047
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of genuine empty follicle syndrome

Abstract: Objective To describe the prevalence of “genuine” empty follicle syndrome and “false” empty follicle syndrome at ART. Design Retrospective cohort. Setting Large private fertility center. Patient(s) 12,359 patients who underwent ART between 2004 and 2009. Intervention(s) None. Main Outcome Measure(s) The failure to recover an oocyte during oocyte retrieval at ART, with and without a detectable serum β-hCG on day of retrieval. Result(s) Two cases of genuine empty follicle syndrome and 9 cases of fals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 31 publications
1
20
0
10
Order By: Relevance
“…Another important aspect of agonist-triggered cycles is the incidence of empty follicle syndrome (EFS). The incidence of EFS has been reported as 0.6%-3.5% in GnRHa trigger cycles, which is similar to that reported (0.1%-3.1%) after an hCG trigger (12,19,(25)(26)(27)(28)(29). Therefore, EFS is not an inherent and exclusive problem to the GnRHa trigger (25) but could be related to human error, abnormalities in the in vivo biological activity of some batches of commercially available GnRHa, hypothalamic dysfunction, or GnRH receptor mutations (23,26,(28)(29)(30).…”
Section: Discussionsupporting
confidence: 85%
“…Another important aspect of agonist-triggered cycles is the incidence of empty follicle syndrome (EFS). The incidence of EFS has been reported as 0.6%-3.5% in GnRHa trigger cycles, which is similar to that reported (0.1%-3.1%) after an hCG trigger (12,19,(25)(26)(27)(28)(29). Therefore, EFS is not an inherent and exclusive problem to the GnRHa trigger (25) but could be related to human error, abnormalities in the in vivo biological activity of some batches of commercially available GnRHa, hypothalamic dysfunction, or GnRH receptor mutations (23,26,(28)(29)(30).…”
Section: Discussionsupporting
confidence: 85%
“…[3][4][5][6][7] A retrospective study of 12,359 individuals who underwent assisted reproductive technology (ART) revealed that the prevalence of GEFS was about 0.016%. 8 Without oocytes for fertilization, these individuals fail to achieve pregnancy after a demanding and expensive medical intervention, resulting in stress to both physicians and the individuals themselves. 9 In this study, we identified a heterozygous missense mutation in ZP3 (MIM: 182889; GenBank: NM_001110354.1) from a large family with multiple women affected by EFS.…”
Section: Efs Can Be Classified As Either False Efs (Fefs) or Genuine mentioning
confidence: 99%
“…3-7 A retrospective study of 12,359 individuals who underwent assisted reproductive technology (ART) revealed that the prevalence of GEFS was about 0.016%. 8 Without oocytes for fertilization, these individuals fail to achieve pregnancy after a demanding and expensive medical intervention, resulting in stress to both physicians and the individuals themselves.9 …”
mentioning
confidence: 99%
“…[16,17] Yanlış hCG uygulaması ve hCG farmakolojik özel-liklerinde bozulma şeklinde açıklanabilir etiyolojisi olduğu gibi hiçbir sebebin bulunamadığı durumlar da olmaktadır. [18] Gonadotropin salgılatıcı hormon (GnRH) antagonisti sikluslarında endojen LH salınımı için GnRH agonisti kullanıldığında boş folikül sendromuyla karşı-laşma oranı %1.4 oranında bildirilmektedir. [19] Bizim ça-lışmamızda tüm final oosit maturasyonu rekombinant hCG ile yapıldı ve boş folikül sendromu oranımız %1.4 idi.…”
Section: Discussionunclassified